2014
DOI: 10.1016/j.juro.2013.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Urinary NGF, TGF-β1, TIMP-2 and Bladder Wall Thickness Predict Neurourological Findings in Children with Myelodysplasia

Abstract: Urine markers and bladder wall thickness measurement may predict urinary tract impairment in children with myelodysplasia. Such markers may differentiate at risk patients with either renal scarring or high detrusor leak point pressure, and decrease the need for urodynamics and renal scintigraphy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
65
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 25 publications
5
65
2
Order By: Relevance
“…Sekerci et al reported that the average of ventral and dorsal BWTs measured at MCC was significantly less in controls than in patients with DLPP 40 cm H 2 O or greater and those with VUR. 7 In the present study no significant differences in ventral BWT measured at Comparison of bladder wall thickness measured at each percent MCC in patients with (red plot) and without (black plot) unfavorable VUDS findings. A, high MDP.…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations
“…Sekerci et al reported that the average of ventral and dorsal BWTs measured at MCC was significantly less in controls than in patients with DLPP 40 cm H 2 O or greater and those with VUR. 7 In the present study no significant differences in ventral BWT measured at Comparison of bladder wall thickness measured at each percent MCC in patients with (red plot) and without (black plot) unfavorable VUDS findings. A, high MDP.…”
Section: Discussioncontrasting
confidence: 42%
“…3,4,7 Because of differences in methodology for measuring BWT, these reports have different results, with 2 studies concluding that BWT measurements are useful for predicting unfavorable findings on VUDS. 4,7 Comparing patients with and without unfavorable UDS parameters, there were no significant differences in BWT measured at various bladder volumes, except for bladder trabeculation. BWT measured at more than 50% MCC was significantly increased in patients with bladder trabeculation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another recent study, in children with myelodysplasia, Sekerci and colleagues investigated the potential value of urinary NGF (and other cytokines such as TGF-β1 and TIMP-2) to predict renal damage caused by high pressure NDO. In fact, patients with DSD in whom bladder emptying only occurred at pressures above 40 cmH2O had remarkably high levels of urinary NGF[96].…”
mentioning
confidence: 96%